A modern mold room: Meshing 3D surface scanning, digital design, and 3D printing with bolus fabrication. Issue 9 (27th August 2019) - Sasaki, David Kiyoshi; McGeachy, Philip; Alpuche Aviles, Jorge E.; McCurdy, Boyd; Koul, Rashmi; Dubey, Arbind
Abstract: Purpose: This case series represents an initial experience with implementing 3‐dimensional (3D) surface scanning, digital design, and 3D printing for bolus fabrication for patients with complex surface anatomy where traditional approaches are challenging. Methods and Materials: For 10 patients requiring bolus in regions with complex contours, bolus was designed digitally from 3D surface scanning data or computed tomography (CT) images using either a treatment planning system or mesh editing software. Boluses were printed using a fused deposition modeling printer with polylactic acid. Quality assurance tests were performed for each printed bolus to verify density and shape. Results: For 9 of 10 patients, digitally designed boluses were used for treatment with no issues. In 1 case, the bolus was not used because dosimetric requirements were met without the bolus. QA tests revealed that the bulk density was within 3% of the reference value for 9 of 12 prints, and with more judicious selection of print settings this could be increased. For these 9 prints, density uniformity was as good as or better than our traditional sheet bolus material. The average shape error of the pieces was less than 0.5 mm, and no issues with fit or comfort were encountered during use. Conclusions: This study demonstrates that new technologies such as 3D surface scanning, digital design and 3D printing can be safely and effectively used to modernize bolus fabrication.